El APQP como una herramienta de mejora para las empresas del sector automotriz (2021)
Currently in a demanding and competitive world, companies in the automotive sector have been forced to implement improvement tools within their practical practices to develop products at lower costs and meeting the proposed quality objectives. One of the most widely used tools within the industry is APQP (Advanced Product Quality Planning), this is a methodology that aims to develop products that meet the needs of the customer, either with a new product or with one already existing within the organization. The objective of this study is to determine, through a review of the literature, the main characteristics and elements of the APQP, the impact generated by its implementation in addition to the advantages, disadvantages and difficulties that can be presented when the methodology is launched.